THE AXIOLOGICAL POTENTIAL OF MASTERING THE ART OF THE LATE 20THAND EARLY 21STCENTURY IN CONTEMPORARY EDUCATIONAL INSTITUTIONS - M.Akishina, Ekaterina (Revista Inclusiones, 2019)
The purpose of the article is to reveal the main aspects of the axiological potential of mastering contemporary art in educational institutions of different types and levels. The authors emphasize that mastering art values is part of the pedagogical influence on the successful socialization of students. Works of art of the late 20thand early 21stcenturies concentrate cultural and social experience, creating an information field rich with facts and emotions. This stimulates the personality of a growing person to self-discovery and valuable interaction with the world. Meanwhile, the complicated language of contemporary art is a significant challenge for education. Urgent problems of uncovering of the axiological potential of mastering contemporary art, identified during the controversy, led to the development of an integrated systemof mastering musical art of the late 20thand early 21stcenturies, in which a central part was occupied by the development of value orientations of students. The article describes this system and analyzes the results of its introduction to practice of a number of educational organizations in Russia